2020
DOI: 10.1177/1078155220947141
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib for treatment in immune-mediated myocarditis: The first reported cases

Abstract: Introduction Immune checkpoint inhibitors (ICI) has demonstrated significant clinical benefit in advanced cancer. Despite favorable benefits, the use of ICI is accompanied by various side effects, which are inflammatory side effects potentially affecting any organ. Among which myocarditis is the most severe and has a relatively high mortality. However, there is no effective treatments, and many patients respond poorly to glucocorticoids and immunosuppressants. Therefore, it is urgent to explore effective treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…For the cases reviewed, the demographic features, clinical manifestations and treatment of irAEs were summarized ( Table 1 ). From these case reports, sintilimab has been shown to induce various immune-associated disorders, including autoimmune diabetes ( 18 , 26 , 30 ), pneumonitis ( 27 , 28 ), pulmonary fibrosis ( 20 ), cytokine release syndrome and multiple organ failure ( 20 , 21 ), myocarditis ( 24 , 29 ), hypothyroid myopathy ( 19 ), myasthenia gravis and myasthenia crisis ( 22 ), paraneoplastic neurological syndrome and enteric neuropathy ( 23 ), psoriasis exacerbation ( 25 ). Some literatures previously indicated that patients with irAEs usually showed a markedly better efficacy than those without irAEs, known as higher overall response rate, longer PFS and better overall survival ( 31 , 32 ).…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…For the cases reviewed, the demographic features, clinical manifestations and treatment of irAEs were summarized ( Table 1 ). From these case reports, sintilimab has been shown to induce various immune-associated disorders, including autoimmune diabetes ( 18 , 26 , 30 ), pneumonitis ( 27 , 28 ), pulmonary fibrosis ( 20 ), cytokine release syndrome and multiple organ failure ( 20 , 21 ), myocarditis ( 24 , 29 ), hypothyroid myopathy ( 19 ), myasthenia gravis and myasthenia crisis ( 22 ), paraneoplastic neurological syndrome and enteric neuropathy ( 23 ), psoriasis exacerbation ( 25 ). Some literatures previously indicated that patients with irAEs usually showed a markedly better efficacy than those without irAEs, known as higher overall response rate, longer PFS and better overall survival ( 31 , 32 ).…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Steroid use is based on its anti-inflammatory action and decreasing inflammation size. In addition to corticosteroid, immunosuppressive agents as infliximab [15, 17, 18, 31, 37, 38], intravenous immunoglobulin (IVG) [11, 13, 22, 24, 37, 38, 41], antithymocyte [35], and plasma exchange [19, 24, 33], and plasmapheresis [36, 38] are used as a secondary treatment after corticosteroid trial. [11] Also, myco-phenolate mofetil (MMF) [27, 28, 30] and tacrolimus [11, 20, 24, 41], tofacitinib [41], and abatacept [32] were used and they helped in the management and controlling the inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to corticosteroid, immunosuppressive agents as infliximab [15, 17, 18, 31, 37, 38], intravenous immunoglobulin (IVG) [11, 13, 22, 24, 37, 38, 41], antithymocyte [35], and plasma exchange [19, 24, 33], and plasmapheresis [36, 38] are used as a secondary treatment after corticosteroid trial. [11] Also, myco-phenolate mofetil (MMF) [27, 28, 30] and tacrolimus [11, 20, 24, 41], tofacitinib [41], and abatacept [32] were used and they helped in the management and controlling the inflammation. The rationale for using infliximab and anti-TNF drug based on IC-induced myocarditis microscopic finding, these drugs decrease T-lymphocyte activity and have been considered for the treatment of myocarditis related to autoimmune or infectious disease, therefore, it is recommended to be used in IC-induced myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Both patients responded poorly to the treatment with steroids, plasma exchange, and intravenous immunoglobulin (IVIG), while they had significant and rapid clinical and biochemical improvement with Tofacitinib, at 5 mg twice daily. Tofacitinib may be a new option for the treatment of refractory ICI-associated myocarditis, but it needs more evidence by randomized clinical trials [ 59 ].…”
Section: Treatment Optionsmentioning
confidence: 99%